The monsters on the bus - Albee, Sarah; Ewers, Joe (New York, NY : Random House, 2022)
A blue monster in a green suit gets on a bus one rainy day, only to be joined by a series of other creatures, each one noisier and more annoying than the next, in a story based on the popular children's song, "The Wheels on the Bus."
On board pages.
Cover title.
"Originally published in slightly different form by Random House Children's Books, New York, in conjunction with sesame Workshop, in 2001."--Cover page 4.
Keywords: Sesame Street (Television program) -- Juvenile fiction; Buses -- Juvenile fiction; Monsters -- Juvenile fiction; Puppets -- Juvenile fiction; Stories in rhyme; Board books; Picture books; Buses -- Fiction; Monsters -- Fiction; Puppets -- Fiction; Stories in rhyme; Board books; Picture books; Stories in rhyme; Board books; Picture books